Ordinances of the City of Bayonne, From 1869 to 1894, at 521 (1894) - (:unkn) unknown (My University, 1888)
An Ordinance to Regulate the Discharge of Firearms within the City of Bayonne, 1-2: That no person shall, within the limits of the City of Bayonne, fire or discharge any pistol, cannon, fowling-piece, duck-gun, rifle, air-gun or other gun, except in the lawful defence of his property, person or family, or set off or explode any squibs, Chinese crackers or other fire-works, except on the Fourth of July, under a penalty not exceeding ten dollars for each offence, to be collected in the manner provided by law; provided, however, that the Council may permit proper parties to engage in the practice of marksmanship under proper restrictions.
Keywords: DISCHARGE